6g-6g+g-1=8

Simple and best practice solution for 6g-6g+g-1=8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6g-6g+g-1=8 equation:


Simplifying
6g + -6g + g + -1 = 8

Reorder the terms:
-1 + 6g + -6g + g = 8

Combine like terms: 6g + -6g = 0
-1 + 0 + g = 8
-1 + g = 8

Solving
-1 + g = 8

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Add '1' to each side of the equation.
-1 + 1 + g = 8 + 1

Combine like terms: -1 + 1 = 0
0 + g = 8 + 1
g = 8 + 1

Combine like terms: 8 + 1 = 9
g = 9

Simplifying
g = 9

See similar equations:

| -4+9=-3 | | 128x-16x^2=0 | | 4x-5=12x+85 | | 14n+2-2n=37 | | 6f-22=24 | | -g+6=-4 | | -(15+9w)-(2w-3z)= | | 58=5a+10-3a | | 8x+4x=344 | | 1081=c(c) | | 1.24-0.2= | | 2r+-4=-2 | | 10z+3z-11z=14 | | 9x-7=5(x+5) | | h+5h-2h=16 | | 3+2n+6n=19 | | 2m-6=2(m+2)-10 | | 3x-(5x-1)+7=22 | | -204.27=8(8x-0.2) | | 23x+15y=130 | | 2x+5-4(1x+3)=-3(1x-3) | | 3r+7r-(-11r)-10r+-12r=20 | | 13x-2+4x-5=180 | | 60h+45h=3000 | | 9-6q=11+5q | | 5(2y+7)-15-15y=-20 | | -x-8+14x=-14 | | 15p-7p-6=2 | | 3D-8=2d-7 | | 5=13n-12 | | 2j=12 | | -n=2n+3 |

Equations solver categories